Detection potential of floating matter in high-resolution X-band SAR data: initial results with visual interpretations - Hadjal, Madjid; Barnes, Brian B.; Hu, Chuanmin; Qi, Lin; Papageorgiou, Dimitris; Topouzelis, Konstantinos (Frontiers in Remote Sensing, 2025)
Remote detection of floating matter, such as macroalgae, plastics, or other debris, primarily relies on the use of passive optical imagery that requires daytime collection and an absence of clouds, sun glint, and thick aerosols. Synthetic aperture radar (SAR) sensors are not affected by these issues, but their capacity in such detection has not been robustly characterized. As such, this study qualitatively evaluates the capacity of Capella Space X-band (9.6 GHz) SAR, which provides data at a spatial resolution of 0.35–1 m, 100 to 800 times higher than what is currently available from Sentinel-1 C-band (5.4 GHz) SAR. A controlled experiment with floating plastic targets of 1 m2, 2 m2, and 3 m2 showed that only the 3 m2 target and 1 m2 mooring buoys were clearly detected and only in a single collection mode. Some macroalgae and floating plants, such as Ulva prolifera and hyacinth, were consistently detected by Capella SAR. However, Sargassum horneri and Sargassum natans/fluitans were only partially detected by Capella SAR, with larger aggregations providing more positive detections. Surface scums of phytoplankton such as Trichodesmium or Noctiluca were not detected. The main detection limitations arise from the weak contrast between the floating matter and the surrounding water, as well as the low signal-to-noise ratios (SNRs) of the three different collection modes of Capella SAR, which range from 2 to 6 (±0.03–0.35). On the other hand, Capella SAR successfully detected floating material in Lake Skadar/Shkodra (Albania and Montenegro) and foam and potential brine shrimp cysts in the Great Salt Lake, while these targets were not detected using Sentinel-1. Despite a limited dataset of only 33 SAR images paired with concurrent and co-located optical images, these preliminary results show the value of high-resolution X-band SAR in detecting relatively large mats of plastics and certain types of macroalgae. The findings can also help task the satellites to collect targeted images for event response.